Effect of roasting conditions on hardness, moisture content and colour of pistachio kernels - Shakerardekani, Ahmad; Karim, Roselina; Mohd Ghazali, Hasanah; Chin, Nyuk Ling (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Roasting of whole-kernels is an important step in the production of pistachio paste. The effect of hot air roasting temperatures (90-190°C) and times (5-65 min) on the hardness, moisture content and colour attributes ('L', 'a' and 'b' values and yellowness index) of both whole-kernel and ground-state were investigated using response surface methodology (RSM). Increases in roasting temperature and time caused a decrease in all the responses except for 'a' value of ground-state. The interaction and quadratic models sufficiently described the changes in the hardness and colour values, respectively. The result of RSM analysis showed that hardness and colour attributes ('L' and 'b' values, yellowness index) of kernels and 'a' value of ground-state could be used to monitor the roasting quality of whole-kernels. This study showed that the recommended range of roasting temperature and time of whole-kernel for the production of pistachio paste were 130-140°C and 30-40 min, respectively.